Property and 'publicness': bishops and lay‐founded churches in post‐Roman Hispania. Issue 2 (11th March 2020) - Addison, David
Abstract : Accounts of how the church fits into broader narratives of socio‐economic change have been confused by two different issues: an unsystematic application of the terms 'public' and 'private' to various phenomena, and a separate tendency to elide the 'public' with the state. Visigothic thought on lay‐founded churches shows that the legal regime around ecclesiastical properties did not aim at simply enhancing episcopal power. Laypeople had important responsibilities and powers, especially in resisting bishops' capacities for 'private' appropriation of donated property. There existed a sense of communal concern for church property, which was thought of as 'public' without reference to the state.